2015
DOI: 10.1115/1.4029322
|View full text |Cite
|
Sign up to set email alerts
|

Study on Minimum Wall Thickness Requirement for Seismic Buckling of Reactor Vessel Based on System Based Code Concept

Abstract: The minimum wall thickness required to prevent seismic buckling of a reactor vessel (RV) in a fast reactor is derived using the system based code (SBC) concept. One of the key features of SBC concept is margin optimization; to implement this concept, the reliability design method is employed, and the target reliability for seismic buckling of the RV is derived from nuclear plant safety goals. Input data for reliability evaluation, such as distribution type, mean value, and standard deviation of random variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Both of dead weight and internal pressure contribute as negative axial compressive load. Therefore, the limit state function, g2, is revised as follows; (19) According to previous studies (Takaya et al, 2015a;Yokoi et al, 2016), the probability distributions of sW and sp are assumed as follows;…”
Section: Incorporation Of Dead Weight and Internal Pressure Into The mentioning
confidence: 99%
See 2 more Smart Citations
“…Both of dead weight and internal pressure contribute as negative axial compressive load. Therefore, the limit state function, g2, is revised as follows; (19) According to previous studies (Takaya et al, 2015a;Yokoi et al, 2016), the probability distributions of sW and sp are assumed as follows;…”
Section: Incorporation Of Dead Weight and Internal Pressure Into The mentioning
confidence: 99%
“…Three combinations of probabilistic distributions shown in Table 2 were considered for sw and sp, according to a previous study (Takaya et al, 2015a): "High", "Low" and "N/A (Not Applied)". Deference in influence of sw and sp by site was also investigated by considering three sites in Table 3: Sites A, B and C. The same seismic conditions were assumed for these sites as in a previous study (Takaya et al, 2017).…”
Section: Evaluation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our previous work (Takaya et al, 2015a), σac and σb are evaluated by the following equations with axial compressive stress due to a design basis earthquake, σac Ss , bending stress due to a design basis earthquake, σb Ss , and the annual maximum earthquake normalized by a design basis earthquake, X;…”
Section: Evaluation Conditions 31 Limit State Functions and Design Ementioning
confidence: 99%
“…Although thicker walls are preferable in terms of prevention of seismic buckling, excessively thick walls introduce large thermal stress causing unacceptable creep-fatigue interaction damage. In a previous study (Takaya et al, 2015a), we proposed an evaluation method for the seismic buckling probability of a reactor vessel considering seismic hazards. It was shown that among the random variables in the evaluation, seismic load had the most significant impact on buckling probability.…”
Section: Introductionmentioning
confidence: 99%